Critical Discourse Analysis of Multicultural Learning at the Early Childhood Education through the Proyek Penguatan Profil Pelajar Pancasila - Maruf, Amrin (LPPM Universitas Muhammadiyah Cirebon, 2025)
This paper explores multicultural learning at the Early Childhood Education (ECE) level implemented through the Proyek Penguatan Profil Pelajar Pancasila (P5) or Pancasila Student Profile Strengthening Project. The analysis is carried out on policy guidelines containing regional content and local wisdom and how the locality relates to Indonesia's national cultural context. This method develops the Critical Discourse Analysis (CDA) approach to understand the relationship between language, power, and ideology in social practices, including critiquing education policies. The results show that the government policy uses a digital teacher guidebook to disseminate the implementation procedures for multicultural content in P5. Content containing multicultural educational values ​​is manifested in the themes “I Love Indonesia” (aku cinta Indonesia) and “We Are All Brothers” (kita semua bersaudara). The theme has values ​​that aspire to local wisdom and train children to appreciate existing differences as a form of the peak of national culture. By examining the implementation of multicultural education in ECE, this paper helps teachers understand policy texts more critically and read more deeply about how a policy is implemented. Educational policy is not value-free, but there are always interests following the objectives of the government/politics being implemented.